Prediksi Laju Sedimentasi dan Erosi di Sub DAS Kemuning Menggunakan Rainfall Simulator - Idah Andriyani; Sri Wahyuningsih; Muhamad Derajat Karim (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2019)
Sedimentation is the accumulation of sediment materials in a location due to both surface erosion and cliff erosion that occurred in the water catchment area, and which was carried by the flow of water to that location. The purpose of this study was to determine the sedimentation rate by using slope data and rainfall intensity in the river basin area. The sample used in this study was the land located in the Kemuning watershed, in which the Kemuning watershed is a sub-watershed of the Bedadung watershed located upstream. Soil samples were taken from 3 different points, upstream, middle and downstream, then the soil was taken to the laboratory to be tested for the soil’s physical properties and the rate of soil loss using a rainfall simulator tool. The research results of soil erodibility in the upstream, middle area and downstream were 0.74 (very high); 0.59 (high); and 0.7 (very high) respectively. Moreover, the calibration of slope in the field to the rainfall simulator was 15°. We found that rainfall intensity which give the highest sedimentation in the upstream, middle and downstream area were 142.15 mm/h; 132.05 mm/h; and 137.43 mm/h respectively, with rainfall durations of 13.88 minutes; 15.50 minutes; and 14.60 minutes. Finally, the sedimentation measurement results using a rainfall simulator in the upstream, middle and downstream were 39904.04 mg/L; middle 85401.85 mg/L; and downstream 75530.00 mg/L respectively. We conclude that rainfall duration gives more influence to the sedimentation.